1998
DOI: 10.1177/030006059802600305
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptability, Efficacy and Safety of a New Paediatric Oral Suspension of Roxithromycin in Respiratory Tract Infections

Abstract: A new paediatric formulation of roxithromycin was tested for acceptability, efficacy and safety in a multicentre, prospective, non-comparative trial in 210 children, aged between 2 and 8 years, with a variety of respiratory tract infections. Most children were diagnosed as having rhinobronchitis, acute pharyngitis or acute tonsillitis. A dose of 5-8 mg/kg/day (mean +/- SD, 5.92 +/- 1.12) roxithromycin was given orally for 5-10 days (mean +/- SDL 6.86 +/- 1.80). The formulation consists of a tablet for suspensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Administration of tablets predispersed on a spoon was reported in two studies; this type of formulation has the benefits of stability of a tablet with the administration being akin to a liquid which is more familiar to some children and offers benefits to younger children. The overall acceptability was good although there were reports of dispersion on the spoon being awkward for parents …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Administration of tablets predispersed on a spoon was reported in two studies; this type of formulation has the benefits of stability of a tablet with the administration being akin to a liquid which is more familiar to some children and offers benefits to younger children. The overall acceptability was good although there were reports of dispersion on the spoon being awkward for parents …”
Section: Resultsmentioning
confidence: 98%
“…The resulting mean scores (of 5) for each drug were the following: cefdinir = 3.97, amoxicillin/clavulanate = 3.37, cefprozil = 3.95 and azithromycin = 3.95, and all products were rated as having an acceptable smell within this study. The percentage of participants agreeing a product was acceptable was also used as a measure within studies, and the lowest percentage in agreement where the product was concluded to be acceptable was 70.5% …”
Section: Resultsmentioning
confidence: 99%
“…For example, understanding the need for medication adherence and subsequent co-operation may differ in the two patient groups, and the taste of a medicine might influence the willingness (or unwillingness) to take a medicinal product in different ways. + (Cohen et al, 2009;Geltman et al, 2009;Klingmann et al, 2013a;Spomer et al, 2012;van Riet-Nales et al, 2013) ± (Dagan et al, 1994;Kekitiinwa et al, 2016;Nahirya-Ntege et al, 2012;Scolnik et al, 2002) -(van Riet-Nales et al, 2015Zlotkin et al, 2003) + (Cohen et al, 2009;Jacobsen et al, 2015b;Klingmann et al, 2013a;Moniot-Ville et al, 1998;Mulla et al, 2016;Spomer et al, 2012) ± (Kekitiinwa et al, 2016;Nahirya-Ntege et al, 2012;Scolnik et al, 2002) -(van Riet-Nales et al, 2015Verrotti et al, 2012) + (Bekele et al, 2014;Cohen et al, 2009;Jacobsen et al, 2015b;Moniot-Ville et al, 1998;Mulla et al, 2016) ±(Nahirya-Ntege et al, 2012) - (Cloyd et al, 1992;Verrotti et al, 2012) + (Cohen et al, 2009) (Bekele et al, 2014) ±(N...…”
Section: Acceptabilitymentioning
confidence: 99%
“…Observations of facial reactions were used in acceptability testing of medicines [63,53,60]. Moniot-Ville et al (1998) used a simple researcher observation of a child, where if the child smiled whilst taking the medicine it was rated as good or fairly good; if the child accepted the medicine without making faces it was rated as acceptable and if the child made faces or complained about the taste this was rated as poor.…”
Section: Observations Of Acceptabilitymentioning
confidence: 99%
“…The amoxicillin reference product was stated to have excellent palatability [43] Acceptable taste = mean score of 3.4/5 Unacceptable taste = mean score of 2.1/5 Two products were included that were stated to be acceptable and unacceptable in terms of taste Acceptable taste was brand W penicillin Unacceptable taste was brand U penicillin [18] Primary endpoint was % of participants with a score of >4/7 85.3 % of subjects found the strawberry flavour lozenge to be acceptable and 49.0 % for the orange flavour lozenge [21] Visual Analogue Scale 50mm point on a 100mm VAS stated to be ambivalent taste, scores above 50 mm are palatable Paracare double strength paracetamol stated to be palatable and acceptable compared to Parapaed [14] Observations/Carer reports A child accepting the drug without making faces or smiling whilst observed taking the medicine 70.5% of children accepted roxithromycin tablet for suspension [63] Observations were used to assess swallowing of the dosage form. Swallowing the dose, even with chewing, was measured as an acceptable formulation Minitablets 2-3 mm in diameter are acceptable to children ≥ 6 months When suspended in jelly up to 10 minitablets are acceptable as a single dose [26,28,27] Carers needed to state that the product was equally or more acceptable to their child than other medicines (70% of population agreeing was used as basis for statistical powering)…”
Section: Compliance With Ethical Standardsmentioning
confidence: 99%